Financial Literacy Among Adults: A Methodology Review and Systematic Review with VOS Viewer Application - Asteria, Beta; Kurnianto Tjahjono, Heru (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2025)
This research aims to test research with the theme of Financial Literacy methodologically and systematically. The methodology research results show that setting the number of samples. The sample technique chosen greatly determines the success of the research. Incorrect sampling produces suboptimal results and cannot be population-specific. The sample selection technique is random or not influenced by the time required to collect data and regulates the logical sample required by the researcher. For example, regional sampling. The research results are based on a systematic review of Scopus journal data; journals searched that meet the journal search requirements with the keywords Literacy, financial, and Young. Journal entry limits with the subject